Tourette’s syndrome - Meita Dhamayanti; Isabella Riandani; Lelly Resna (Paediatrica Indonesiana, 2004)
The aim of this report was to show that mostbehavioral disorders need multidisciplinary manage-ment by behaviorist, neurologist, psychiatrist, psy-chologist and pedagogue, and to give more informa-tion about Tourette’s syndrome so that it can be de-tected earlier. Therefore, children who suffer from itcan live a better life and develop their ability.